Bahasa Sampah di Tempat Bukan Sampah (Kajian Sosiolinguistik) - Rudi Tawari; Nurfani Nurfani; Farida Maricar (LPPM Universitas Bumigora Mataram, 2022)
This article aims to describe the phenomenon of using language in making a ban on throwing garbage by the people of Ternate. The prohibitions on throwing garbage in the form of boards or announcements are scattered in various locations in Ternate City. Data on this prohibition is limited to the community, not offices. Data collection is done by observing directly at locations where there is a prohibition on throwing garbage. Meanwhile, the data related to the public's views on the board or banner for the prohibition of throwing garbage was carried out in two ways, namely direct interviews and indirect interviews. Direct interviews were conducted by going directly to the community around the place where the boards or banners were installed. Meanwhile, indirect interviews were conducted by asking questions using the google form. This research can be said that the variety of language used in the board or ban on the prohibition of waste is a combination of formal and semi-formal variety, semi-formal variety, and non-formal variety. Language that uses swearing is included in the informal variety. Based on reference to language use, all notice boards prohibiting the disposal of garbage using animal references. Meanwhile, the cause of the emergence of a ban on throwing garbage is a long process of population growth which has an impact on increasing waste production, the availability of trash cans, behavior in disposing of garbage, until the emergence of language for garbage that is conveyed in the form of a board or banner prohibition of throwing garbage. Keywords: Variety of Languages, reference to language use for garbage, garbage rohibition